HUBUNGAN ANTARA KOMUNIKASI DENGAN IMPLEMENTASI MANAJEMEN BBLR SEHAT OLEH BIDAN DESA DI KABUPATEN PURBALINGGA - Ema Wahyuningrum (Universitas Harapan Bangsa Purwokerto, 2016)
The incidence of Low Birth Weight Baby (LBWB) and the neonatal mortality rate caused by LBW in Purbalingga District at 2010-2012 was high, although almost allof LBWBs classificated as Healthy. Healthy LBWB management was one of effortsto improve Healthy LBWB service quality in order to reduce infant mortality rate dueto LBWB. The study obective was to analyse factors affecting the implementation ofhealthy LBWB by village midwives in Purbalingg District. This was an observationalanalytic study with a cross sectional approach. The population were all of villagemidwives who attained LBWB management training. Subjects were 36 villagemidwives who were randomly selected from all Primary Health Centre inPurbalingga. The collecting data was held by interview with a structuredquestionnare and observations. The dependent variables was the implementation ofhealthy LBWB management; independent variables were communication, resources(staff and funding), disposition and bureaucracy structure. Chi Square, Fisher’sExact tests were used in data analysis. Results of the study showed that the averageage of midwives were 33.1±.,5 years and the average working period of midwiveswere 11.2±5.5 years. All of the midwives has graduated from midwifery academics(DIII). The Implementation of LBWB healthy management is mostly good (72,2%),communication is mostly good (55,6%), Communication (p=0.002) associated to theimplementation of Healthy Low Birth Weight Baby Management. Keywords : Communication, Implementation, management of healthy low birthweight baby, village midwives.